Building Information Modelling: Present realities and Future possibilities - Pogorelskiy, Sergey; Alava, Diego (International Journal of Engineering and Management Sciences, 2018)
BIM (Building Information Modelling), a term that is drawing the attention worldwide in the construction industry and governments, is a complex concept that involves management effort, tools and applications for enhancing information flow and therefore productivity for projects. This article pretends to briefly explain BIM, its advantages, challenges and potentialities while considering the current adoption of the concept in some countries. Furthermore, the article includes suggestions for the implementation of BIM in an organization as well as in projects and a list with some useful tools for this purpose.